Effectiveness of a plasma treatment device on microbial air quality in a hospital ward, monitored by culture. (February 2021) - Fennelly, M.; O'Connor, D.J.; Hellebust, S.; Murphy, N.; Casey, C.; Eustace, J.; Plant, B.J.; Sodeau, J.R.; Prentice, M.B.
Summary: This study analysed the effectiveness of plasma treatment on airborne bacteria and surface counts during a 14-day intervention within a four-bedded bay in an adult respiratory ward at Cork University Hospital, Ireland. One-hundred-litre air samples were collected twice daily every weekday for 4 weeks, with settle plates and surface swabs. The plasma treatment did not have an effect on airborne bacteria and fungi that was detectable by culture. However, the possibility that culture-based sampling may be insufficiently sensitive to detect an effect, or that the duration of the study was insufficient for plasma treatment to affect a complex environment, cannot be excluded.